Building Social Networks for Health Promotion: Shout-out Health, New Jersey, 2011 - Pamela Rothpletz-Puglia, EdD, RD; Veronica M. Jones, MPH, CHES; Deborah S. Storm, MSN, PhD; J. Scott Parrott, PhD; Kathy Ahearn O'Brien, MPH (Centers for Disease Control and Prevention, 2013)
Background Building social networks for health promotion in high-poverty areas may reduce health disparities. Community involvement provides a mechanism to reach at-risk people with culturally tailored health information. Shout-out Health was a feasibility project to provide opportunity and support for women at risk for or living with human immunodeficiency virus infection to carry out health promotion within their informal social networks. Community Context The Shout-out Health project was designed by an academic-community agency team. During 3 months, health promotion topics were chosen, developed, and delivered to community members within informal social networks by participants living in Paterson and Jersey City, New Jersey. Methods We recruited women from our community agency partner's clients; 57 women participated in in-person or online meetings facilitated by our team. The participants identified and developed the health topics, and we discussed each topic and checked it for message accuracy before the participants provided health promotion within their informal social networks. The primary outcome for evaluating feasibility included the women's feedback about their experiences and the number of times they provided health promotion in the community. Other data collection included participant questionnaires and community-recipient evaluations. Outcome More than half of the participants reported substantial life challenges, such as unemployment and housing problems, yet with technical support and a modest stipend, women in both groups successfully provided health promotion to 5,861 people within their informal social networks. Interpretation Shout-out Health was feasible and has implications for building social networks to disseminate health information and reduce health disparities in communities.